Groundwater Pollution Risk Control from an Industrial Economics Perspective A Case Study on the Jilin Section of the Songhua River - Huan, Huan (Springer Singapore, 2018)
This book argues that groundwater pollution risk assessment is the essential foundation of groundwater pollution prevention and control. It is on this basis that economic leverage is used to make new breakthroughs in groundwater protection and governance. Presenting a case study on the Jilin Section of the Songhua River, the book applies the overlay index method to assess the shallow groundwater pollution risk and identify high-risk areas and major pollution sources in an effort to identify the mechanism of interaction between industrial structures and groundwater pollution. Further, it proposes concrete measures for preventing and controlling groundwater pollution from an industrial economics perspective. As such, the book offers a valuable resource for all graduate students, lecturers and researchers who are interested in learning about resources and environmental economics.